Antibacterial peptide CyclomarinA creates toxicity by deregulating the Mycobacterium tuberculosis ClpC1-ClpP1P2 protease - Taylor, Gabrielle; Frommherz, Yannick; Katikaridis, Panagiotis; Layer, Dominik Christian; Sinning, Irmgard; Carroni, Marta; Weber-Ban, Eilika; Mogk, Axel (The journal of biological chemistry, 2022)
The ring-forming AAA+ hexamer ClpC1 associates with the peptidase ClpP1P2 to form a central ATP-driven protease in Mycobacterium tuberculosis (Mtb). ClpC1 is essential for Mtb viability and has been identified as the target of antibacterial peptides like CyclomarinA (CymA) that exhibit strong toxicity toward Mtb. The mechanistic actions of these drugs are poorly understood. Here, we dissected how ClpC1 activity is controlled and how this control is deregulated by CymA. We show that ClpC1 exists in diverse activity states correlating with its assembly. The basal activity of ClpC1 is low, as it predominantly exists in an inactive nonhexameric resting state. We show that CymA stimulates ClpC1 activity by promoting formation of supercomplexes composed of multiple ClpC1 hexameric rings, enhancing ClpC1-ClpP1P2 degradation activity toward various substrates. Both the ClpC1 resting state and the CymA-induced alternative assembly state rely on interactions between the ClpC1 coiled-coil middle domains (MDs). Accordingly, we found that mutation of the conserved aromatic F444 residue located at the MD tip blocks MD interactions and prevents assembly into higher order complexes, thereby leading to constitutive ClpC1 hexamer formation. We demonstrate that this assembly state exhibits the highest ATPase and proteolytic activities, yet its heterologous expression in Escherichia coli is toxic, indicating that the formation of such a state must be tightly controlled. Taken together, these findings define the basis of control of ClpC1 activity and show how ClpC1 overactivation by an antibacterial drug generates toxicity.
Online veröffentlicht am 26. Juni 2022, Artikelversion vom 29. Juli 2022
Gesehen am 05.09.2022